Designing with Users: A Participatory Design as a Community Engagement Program in the City Zoo - Lukito, Yulia Nurliani; Kusuma, Nevine R; Arvanda, Enira; Ummah, Zafira R (UI Scholars Hub, 2021)
This article discusses a participatory design project that aims at creating a collaborative design among architectural students, visitors, and zoo management in designing street furniture and selfie spots in city zoos. Participatory design is used in the design process to get the users’ and designers’ interpretation of the space, improve design outcomes, and increase the community awareness of their surroundings. As part of the Universitas Indonesia Community Engagement Program, the zoo design project fosters a collaborative design between the university and zoo community and supports the educational, conservational, and recreational goals of Ragunan Zoo in Jakarta. Designing street furniture and selfie spots can hopefully be parts of improving the quality of public space in the zoo. Students and lecturers who usually have limited opportunity to collaborate now have a chance to interact with visitors and the zoo management during the research and design stages while visitors actively collaborate in informing their needs and perception of the space. The zoo management also provides information on their goals and missions so that students can develop and convert the education, conservation, and recreation goals of the zoo into designs. In conclusion, the participatory design approach applied in the zoo design not only allows students to deal with real-life issues in design but also enhances space quality through community participation.